Chronic Consumption of Low-Fat Diet Leads to Increased Hypothalamic Agouti-Related Protein and Reduced Leptin - Staszkiewicz, Jaroslaw (2007)
OBJECTIVE: The study was performed to examine the hypothesis that dietary fat under ad libitum feeding conditions influences the expression levels (mRNA) of the mouse AgRP, leptin, leptin receptor (OBRb), and NPY at early stages of development. RESEARCH METHODS & PROCEDURES: C57Bl/6J male mice were placed on either High Fat Diet (HFD) or Low Fat Diet (LFD) shortly after weaning. Groups of mice were euthanized at various ages and real-time one-step RT-PCR was used to analyze the gene expression in the hypothalamus (AgRP, NPY, OBRb), the adrenal gland (AgRP), the testis (AgRP), and epididymal fat (leptin) RESULTS AND CONCLUSIONS: Leptin expression increased linearly with age but only under the HFD despite body-weight gain under both diets. This pattern of expression coincided with reduced expression of hypothalamic AgRP under HFD, while OBRb and NPY did not fluctuate in response to diet. By contrast, consumption of LFD (i.e. high carbohydrate) increased hypothalamic AgRP and suppressed adipose leptin which is consistent with the notion that leptin could regulate AgRP centrally. In contrast, AgRP expression in the adrenal gland initially decreased and then increased with age, under both diets, suggesting that dietary fat could have a tissue-dependent effect on AgRP that may be unfettered by leptin under the HFD.